Genome-Wide Characterization and Analysis of Expression of the Histone Gene Family in Razor Clam, Sinonovacula constricta - Jiaying Lian; Liyuan Lv; Hanhan Yao; Zhihua Lin; Yinghui Dong (Fishes, 2021)
The Chinese razor clam (Sinonovacula constricta), a bivalve species widely distributed in estuaries and mudflats, is often exposed to extreme environmental and microbial stresses. Histones are fundamental components of chromatin and play an important role in innate immunity, as demonstrated by its antimicrobial activities in clams. However, little attention has been paid to histones in bivalves. To fill this gap, we investigated the genomic distribution, structural characteristics, conserved motifs, and phylogenetic relationships of histones in S. constricta. A total of 114 histone genes were detected in the S. constricta genome, which were divided into 25 types in phylogenetic analysis. Among them, partial histones exhibited a tissue-dependent expression pattern, indicating that they may be involved in sustaining the homeostasis of organs/tissues in adult S. constricta. Furthermore, mRNA expression of certain histones changed significantly in S. constricta when infected with Vibrio parahaemolyticus, suggesting that histones play a role in the immune defense of S. constricta. All together, this study on histone genes in S. constricta not only greatly expands our knowledge of histone function in the clam, but also histone evolution in molluscs.